Pengaruh Kepuasan Upah dan Lingkungan Kerja terhadap Turnover Intention Pada Karyawan UD SGK Kesamben Blitar Jawa Timur - Refani Afri Zaldi (Fakultas Teknik Universitas Negeri Malang, 2019)
This research discussed the effect of wage and work environment satisfaction on turnover intention of the employees from a manufacturing company that is engaged in wood processing, UD SGK, that is located in Kesamben, Blitar, East Java. The turnover intention in UD SGK was highly rated and was increasing per year, and it would influence the company productivity in the future. This research used a saturated sample technique which was all 35 production employees of UD SGK. The data was collected using a questionnaire and using simple linear regression. The results showed that: (1) employees satisfaction in wage in UD SGK was adequate, the work environment in UD SGK was in a low condition, and the turnover intention of UD SGK employees was in the high category, (2) wage satisfaction negatively and significantly influence the employees turnover intention, and (3) work environment negatively and affect the employees turnover intention substantially.